Policy implications of high food prices for Africa: IFPRI 2007-2008 Annual Report Essay - Ngongi, Namanga (International Food Policy Research Institute, 2008)
African agriculture is at a crossroads. The current high food prices and the instability they have provoked in several countries have added impetus for African countries to review their agricultural policies and programs. New agricultural policies will have to be more focused on staple food crops and on their main producers-smallholders, most of whom are women. The new policies must remove constraints that impede access by smallholder farmers to the knowledge, technology, and financial services they need to increase farm productivity in a profitable and environmentally sustainable manner. Institutional mechanisms that lower the risks of lending to the agriculture sector and to smallholders in particular should be established and programs developed to leverage financial resources from the commercial banking sector. Governments and the private sector have an opportunity to work together to support the procurement, blending, and packaging of fertilizers. Together they can also support the breeding and multiplication of improved seeds. Government policies should support agro-dealers to ensure that improved seeds and other inputs are available to farmers. The many issues that African countries must address will be beyond the capacity of most countries, even after financial resources in private banks are leveraged. External assistance will be very much needed, especially to develop essential road infrastructure, irrigation, and rural energy. Other issues, including land policy, will also need attention. The road ahead for African agricultural development, especially the attainment of food security, will not be easy. African governments will need to formulate and implement bold pro-poor, pro-smallholder farmer policies that will increase farm productivity, trigger a sustainable green revolution, and end the cycle of food crises in Africa.